THE RELATIONSHIP BETWEEN THE ROLE OF CURRENT ISSUES/MEDIA AND LOCAL LEADERSHIP/CANDIDATES WITH YOUTH PERCEPTION TOWARDS BARISAN NASIONAL IN BATU PAHAT PARLIAMENTARY CONSTITUENCY. CASE STUDY: THE 14TH GENERAL ELECTION - Ani, Fauziah Binti; Siam, Nur Wasila Binti (International Journal of Psychosocial Rehabilitation, 2020)
The defeat of Barisan Nasional (BN) during the 14th General Elections (GE-14) at the majority of youth voting streams shows youth rejection of BN at the Batu Pahat parliamentary constituency, even though the party introduced out many programmes and assistance for these groups before GE-14. Youth perception, which mainly led to this decision, was influenced by a multitude of factors, among them were media influence and BN local leadership in the area. This paper studies the relationship between the role of media and local leadership, with youth perception towards BN at the Batu Pahat parliamentary constituency. 396 voters under 40 years old were selected as respondents, using a random sampling method. The data is collected through questionnaires, and analysed with the Pearson Correlation Product Moment (Correlation) supported by the SPSS software. The findings show that the role of new media as well as the failure of the local BN leadership were factors with significant relationship with youth perception of BN. This study suggests to the BN party to portray an image that is cleaner and with more integrity, and put forward younger candidates able to voice out youth voices to a more prominent stage. Both the UMNO and Barisan Nasional party machinery must also show wisdom in addressing national issues and issues close to the people, namely leadership image and economic concerns.